Arbitrary Disciplinary Sanctions and the Legal Framework for Their Redress in the Kingdom of Saudi Arabia: An Analytical Study - Danyah Talal Atteiah; Amal Shalabi Khadragey (International Journal of Law Research and Studies, 2026)
The disciplinary authority granted to the employer constitutes one of the mechanisms established in the Saudi Labor Law to maintain order within the establishment. However, this authority is not absolute; it is exercised within the framework of statutory controls and limitations designed to protect workers and safeguard their rights. From this perspective, the present study addresses arbitrary disciplinary penalties and the criteria for addressing them under the legal system of the Kingdom of Saudi Arabia. It elucidates the concept of disciplinary penalties and their statutory basis, delineates the boundaries of the employer’s authority to impose such penalties, and examines the notion of abuse in the exercise of disciplinary authority, along with the criteria by which arbitrariness in disciplinary penalties may be established. The study further explores the safeguards prescribed by the Saudi regulator to shield workers from arbitrariness in the imposition of disciplinary penalties—whether substantive safeguards, such as the legality of the penalty and its proportionality to the violation, or procedural safeguards, such as conducting an investigation, hearing the worker’s defense, and enabling them to lodge an internal grievance in accordance with the prescribed statutory procedures. The study concludes that the Saudi regulator has confined disciplinary penalties to specific categories stipulated by statute and has enveloped them with a suite of safeguards aimed at achieving justice and equilibrium between the parties to the employment relationship. It further establishes that arbitrariness arises whenever a disciplinary penalty deviates from its legitimate purpose, occasions unjustified harm to the worker, or is imposed in contravention of the prescribed statutory procedures—thereby helping to curb abuses of disciplinary authority within the workplace.